2016
DOI: 10.18632/oncotarget.8691
|View full text |Cite
|
Sign up to set email alerts
|

Sequential intensified conditioning followed by prophylactic DLI could reduce relapse of refractory acute leukemia after allo-HSCT

Abstract: The major obstacle is leukemia relapse for refractory leukemia undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT). We previously introduced a strategy of sequential intensified conditioning and early rapid immunosupressant withdrawal for refractory leukemia undergoing allo-HSCT, with 5-year overall survival (OS) and 3-year relapse rate of 44.6% and 33.3%. To reduce leukemia relapse, prophylactic donor lymphocyte infusion (DLI) was administered based on our historical strategy. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…Recently, some studies showed that intensified conditioning followed by allo-HSCT could achieve acceptable outcomes for refractory leukemia [5][6][7][8][9]. In our transplant center, a strategy of sequential intensified conditioning followed by donor lymphocyte infusion (DLI) was implemented since 2009, and encouraging outcomes were reported previously [10].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Recently, some studies showed that intensified conditioning followed by allo-HSCT could achieve acceptable outcomes for refractory leukemia [5][6][7][8][9]. In our transplant center, a strategy of sequential intensified conditioning followed by donor lymphocyte infusion (DLI) was implemented since 2009, and encouraging outcomes were reported previously [10].…”
Section: Introductionmentioning
confidence: 86%
“…Ciclosporin A (CsA) + methotrexate (MTX) were administered in patients undergoing MSD transplants for GVHD prophylaxis. CsA + MTX + antithymocyte globulin (ATG) and mycophenolate were used in patients receiving HID [10].The total dose of ATG (rabbit antihuman thymocyte immunoglobulin, ImtixSangstat, Lyon, France) was randomly assigned as 7.5 mg/kg from days − 3 to − 1 or 10.0 mg/kg from days − 4 to − 1 in one trial (NCT01883180), and just 10.0 mg/kg from days − 4 to − 1 for all patients in another trial (NCT02673008).…”
Section: Conditioning and Transplantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the two groups (80 DLI versus 64 non-DLI), the relapse rate was less and OS was superior in patients receiving DLI than in those without DLI administration (22.7% vs. 33.9%, p = 0.048; 58.1% vs. 54.9%, p = 0.043). In a multivariate analysis, DLI and cGvHD were associated with less relapse and improved OS [68].…”
Section: Flamsa-ric and DLImentioning
confidence: 93%